Improving reliability of the trucks - Iskhakov, Arthur; Makarova, Irina; Khabibullin, Rifat (Видавництво Львівської політехніки, 2013)
In the article the ways of increasing competitiveness automotive technique and providing opportunities improving them by analyzing information about defects with principle of "feedback" are analyzed. Used methodology of systems allows to organize interaction between systems of firm service and production system to improve efficiency of interaction.
Keywords: automotive technique; increase of reliability; system of firm service; frame of the truck; stress-strain state